A bibliometric analysis reveals a dynamic growth in the use of artificial intelligence in oral cancer research over three decades - Irna Sufiawati; Anisa Insyafiana; Rifat Rahman; Adi Idris (Discover Oncology)
Abstract Oral cancer (OC) remains a significant malignant neoplasm in both the developed and developing world. Artificial intelligence (AI) has had a significant impact on scientific disciplines, including oncology by transforming data analysis and predictive capabilities. Recent advancements in AI have enabled researchers to integrate and synthesize multidimensional datasets, infer patterns, and predict outcomes, ultimately enhancing shared decision-making between patients and clinicians. This bibliometric analysis aims to provide a comprehensive overview of the application of AI in OC research over the last three decades. Our analysis of 351 articles retrieved from SCOPUS between 1998 and 2024 using VOSviewer highlights the dynamic growth of AI in OC research. The significant trends in publications and citations reflect the increasing interest and impact of this field. These findings provide valuable insights for policymakers, funding agencies, and researchers, guiding future efforts to integrate AI technologies into oral oncology practices.